2013
DOI: 10.1597/11-207
|View full text |Cite
|
Sign up to set email alerts
|

Scoring Systems of Cleft-Related Facial Deformities: A Review of Literature

Abstract: Objective :  There is a need for an internationally agreed objective method of assessing cleft-related deformities in order to compare the results of individual surgeons and different surgical techniques or to determine the optimal timing for primary lip closure. To assess the current methods, an overview of the recent developments in postoperative scoring systems of cleft-related deformities was made. Methods :  A Medline search from June 2003 through July 2011 was conducted, and references in the selected ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
54
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 65 publications
4
54
1
Order By: Relevance
“…Depending on the complexity of the pathology, CL/P patients require a multidisciplinary approach in order to ameliorate functional, social and psychological aspects of their life. Generally, patients are longitudinally submitted to several types of treatments, comprising orthopedic and surgical procedures [2,3]. In particular, the orthopedic treatment, performed with active and passive acrylic plates, can help to align the cleft segments and facilitate surgery [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the complexity of the pathology, CL/P patients require a multidisciplinary approach in order to ameliorate functional, social and psychological aspects of their life. Generally, patients are longitudinally submitted to several types of treatments, comprising orthopedic and surgical procedures [2,3]. In particular, the orthopedic treatment, performed with active and passive acrylic plates, can help to align the cleft segments and facilitate surgery [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“… 25 28 The Asher-McDade system for evaluating nasolabial appearance has limitations, including subjectivity and imperfect agreement among clinicians. 11 , 13 , 22 , 29 This study’s limited sample also reduced the ability to detect small differences in nasolabial appearance. Whether the study’s results reflect cleft care delivery across North America will need to be determined in future studies with a larger, more diverse sample of patients.…”
Section: Discussionmentioning
confidence: 98%
“…Using a continuous VAS to score overcomes these issues and provides greater statistical sensitivity. A recent systematic review concluded that there remained a lack of consensus as to a reliable, validated and reproducible scoring system, a situation that still effectively exists as evidenced by a more recent study of 3D assessment methods which suggested 2D and 3D methods were measuring different nasolabial aspects . Currently, the use of 3D imaging is not common in NZ and as yet there is little methodology data on its assessment worldwide.…”
Section: Discussionmentioning
confidence: 99%